Defining Length Stability in Paediatric Femoral Shaft Fractures Treated with Titanium Elastic Nails. (December 2021) - Shieh, Alvin K.; Saiz, Augustine M.; Hideshima, Kelsey S.; Haus, Brian M.; Leshikar, Holly B.
Introduction: Optimal paediatric femoral shaft fracture patterns or lengths amenable to titanium elastic nail stabilization have not been well defined. The purpose of this study is to identify radiographic parameters predictive of treatment failure with flexible intramedullary nails based upon fracture morphology. Methods: A retrospective review was performed of all femoral shaft fractures treated with flexible intramedullary nails over a five-year period. All patients with at least six weeks of postoperative radiographic imaging were included. Fracture characteristics included location, pattern, length, obliquity, angulation, translation and shortening. Postoperative radiographs were reviewed to determine shortening and angulation. Results: There were 58 patients with 60 femoral shaft fractures stabilized with titanium nails, with 46 healing within acceptable parameters and 14 considered malunions. Six of the 14 malunions developed complications requiring early unplanned intervention. No patients in the treatment success group had a complication. Between the treatment success and failure groups, fracture pattern, location, length, obliquity, angulation, translation or shortening were not statistically different. Mean nail canal fill was significantly lower in the failure group (0.72 versus 0.81; p = 0.0146), with a receiver operating characteristic curve identifying canal fill 76% as the optimal threshold. Conclusion: This is the first study to measure the length and obliquity of paediatric femoral shaft fractures and to determine their relationship to radiographic alignment after healing. None of the preoperative fracture characteristics were predictive of malalignment or shortening. We recommend the use of larger nail sizes in the treatment of paediatric femoral shaft fractures, especially if there is concern for residual instability. Level of evidence: IV